Bunion: The non-surgical approach of treatment - Kakde, Mrunmayi (Indian Journal of Integrative Medicine, 2021)
Background: The bunion is a common malformation pervaded by progressive lateral deviation of the great toe at the first metatarsophalangeal joint. Sometimes it is painful. Many research article claims that surgery is the only treatment that can get rid of bunions. Objective: The objective of this review is to investigate the various non-surgical treatments for the bunion. Methods: Pubmed and Google Scholar were searched for relevant information regarding various non-surgical treatments and methods to treat the bunion. Results: A total of 11 articles were selected for review which included information about the treatments for the bunion and their importance. Conclusion: As surgery for bunions is not adequately restoring the condition of patient and long-term pain often results after surgery, non-surgical treatments for bunions should be more explored and studied for scientifically proven and accepted treatments. Ayurveda and yoga still lack the infallible treatment for the same.